2017
DOI: 10.37761/rsqp.v83i1.106
|View full text |Cite
|
Sign up to set email alerts
|

CATALIZADORES BASADOS EN NixFe1-xO4 PARA LA DESHIDROGENACIÓN OXIDATIVA DEL ETANO A ETILENO

Abstract: Se prepararon catalizadores basados en óxidos mixtos de NixFe1-xO4 (x=0,5 a 0,9) por coprecipitación para la deshidrogenación oxidativa (ODH) del etano y se caracterizaron por difracción de rayos X (XRD), sorción de N2 (método BET), reducción a temperatura programada (TPR) y espectroscopia láser Raman (LRS). La reacción deshidrogenación oxidativa (ODH) del etano se realizó en un reactor de lecho fijo para una relación constante W/F de 0,48 g.s/mL. La sustitución parcial del Ni+2 por Fe+3 en la red produjo la f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Schuurman et al [23] also showed that the ethylene oxidation activity of NiO is lower than its ethane oxidation activity, thus explaining its interesting catalytic behavior in ethane ODH and demonstrating the potential of NiO-based systems in this reaction. A high number of studies focusing on ethane ODH over both unsupported and supported [41][42][43][44][53][54][55][56][57][58][59][60][61][62][63][64] NiO-based catalysts have been published till date and is discussed in detail below.…”
Section: Promoted Bulk Nio Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schuurman et al [23] also showed that the ethylene oxidation activity of NiO is lower than its ethane oxidation activity, thus explaining its interesting catalytic behavior in ethane ODH and demonstrating the potential of NiO-based systems in this reaction. A high number of studies focusing on ethane ODH over both unsupported and supported [41][42][43][44][53][54][55][56][57][58][59][60][61][62][63][64] NiO-based catalysts have been published till date and is discussed in detail below.…”
Section: Promoted Bulk Nio Catalystsmentioning
confidence: 99%
“…The ability of iron to easily change its oxidation state (Fe 2+ ↔ Fe 3+ ), the acidic character of Fe 3+ as well as its similar radius compared to nickel, makes it a good candidate for creating a Ni-Fe mixed oxide. Hurtado Cotillo et al [43] used Fe as a dopant for NiO with good results: in the ODH reaction the catalysts with 10 and 20 at.% Fe have emerged as the best ones. The Ni-Fe-O with 20 at.% Fe exhibits a selectivity of 84% with 7% conversion at 300 °C.…”
Section: Promoted Bulk Nio Catalystsmentioning
confidence: 99%